Tata Kelola pada Badan Usaha Milik Negara: Apakah Berpengaruh Terhadap Penghindaran Pajak? - Irawan, Arry; Suwondo, Sulistia; Kusumastuti, Endah Dwi; Setiawan, Setiawan (Indonesian Accounting Literacy Journal, 2024)
Indonesia has been adversely affected by tax avoidance practices carried out by both corporate and individual taxpayers. Therefore, it is crucial to control tax avoidance from within companies by implementing good corporate governance that ensures compliance with the law and prevents tax avoidance practices that violate regulations. This study aims to explore the influence of corporate governance on tax avoidance in State-Owned Enterprises (SOEs) listed on the Indonesia Stock Exchange. This quantitative research utilizes secondary data from the financial statements of companies listed on the Indonesia Stock Exchange from 2016 to 2022. The independent variables in this study are the number of directors, the number of commissioners, and the proportion of independent commissioners, while the dependent variable is tax avoidance. The study's findings reveal that the number of directors and commissioners have a positive impact on tax avoidance, whereas the proportion of independent commissioners has a negative and significant impact on tax avoidance.